Photo of Jerome Downey, Karen Farrell and woman with book "Jerome: Just One More Song" - Bennett, Margaret (2012)
Photo of singer Jerome Downey with Karen Farrell and an unidentified woman posing with Margaret Bennett's book "Jerome: Just One More Song: Local, Social & Political History in the Repertoire of a Newfoundland-Irish Singer"